The Role of Motivation Mediates the Influence of Work Environment and Leadership on Organizational Commitment - Kurnia, Efry; Aisha, Novi; Sari, Roza Maya; Hidayat, Rahmat (AIBPM Publisher, 2023)
The importance of commitment to employees who can have a positive impact on the development and progress of the company. So there needs to be a driving factor as a good motivation in the work environment. For this reason, there needs to be motivation in moving employees, especially in the work environment. This study aims to explain the role of motivation in mediating the influence of the work environment and leadership that can affect employee commitment in achieving employee and company performance. Conducting this initial survey will explain the causation that can affect other variables. This research was conducted at PT. Cisadane Sawit Raya (CSR), North Sumatera by involving all 76 employees in 2 work units in office with the criteria of working period of ± 5 years with a saturated sampling method. The results of this study can be seen through motivation as a mediation of the influence of the work environment and leadership on organizational commitment that can help companies in identifying.